1976
DOI: 10.1172/jci108406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immunotherapy on humoral and cellular responses in ragweed hayfever.

Abstract: A B S T R A C T The effect of specific immunotherapy on several in vitro responses to ragweed antigen E has been evaluated in 17 atopic patients with ragweed hayfever. The methods employed were leukocyte histamine release, measurement of specific IgE anti-ragweed antibody and specific IgG anti-ragweed antibody, lymphocyte proliferation, and the production of two lymphocyte mediators (migration inhibitory factor and mitogenic factor). The duration of treatment and symptom improvement were also recorded for comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2

Year Published

1979
1979
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(57 citation statements)
references
References 29 publications
(37 reference statements)
4
51
2
Order By: Relevance
“…These include an increase in allergen-specific immunoglobulin (Ig)G antibodies [2] and moderate impairment in the synthesis of allergen-specific IgE [3], development of anti-idiotypic antibodies [4], re-duced basophil reactivity and sensitivity to allergens [2], reduced allergen-stimulated lymphocyte proliferation and lymphokine production [5,6], and the generation of allergen-specific suppressor T-cells [7].…”
mentioning
confidence: 99%
“…These include an increase in allergen-specific immunoglobulin (Ig)G antibodies [2] and moderate impairment in the synthesis of allergen-specific IgE [3], development of anti-idiotypic antibodies [4], re-duced basophil reactivity and sensitivity to allergens [2], reduced allergen-stimulated lymphocyte proliferation and lymphokine production [5,6], and the generation of allergen-specific suppressor T-cells [7].…”
mentioning
confidence: 99%
“…It has been suggested that selective stimulation of Ts cells or a new formation of antigen-specific Ts cells (20)(21)(22) may be responsible for suppressing IgE synthesis during immunotherapy. In man, isotype-as well as antigen-specific Ts cells have been found in patients treated with immunotherapy, but not in untreated controls (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, specific IT with grass–pollen extracts led to a decrease in the production of histamine–releasing factor by mononuclear cells in grass pollen–allergic individuals [9]. Specific IT in ragweed–allergic individuals decreased antigen–specific serum IgE and increased antigen–specific IgG [10]. IT is also associated with an increase in IgG and IgA found in the nasal secretions of allergic individuals [11].…”
Section: Introductionmentioning
confidence: 99%